New data on the distribution of six morphologically cryptic species of Niphargus stygius species complex (Amphipoda: Niphargidae) - Janko Šet; Špela Borko (Natura Sloveniae)
Subterranean amphipods, morphologically resembling Niphargus stygius species complex, were molecularly analysed. We isolated genomic DNA and amplified the subunit I of mitochondrial cytochrome oxidase gene (COI) for 94 specimens from 37 localities. We report on six new localities for N. chagankae, one for N. cvajcki, eight for N. gottscheeanensis, two for N. kenki, one for N. malagorae and two for N. zagrebensis. New data extend previously known distribution ranges of N. gottscheeanensis and fill the missing gap between the remote N. kenki occurrences. We report on new co-occurrence data for two species pairs, i) N. chagankae and N. likanus, and ii) N. gottscheeanensis and N. podpecanus.